CHARACTER EDUCATION INTERVENTION IN PRIMARY SCHOOL: A LITERATURE REVIEW AS A FOUNDATION FOR COMMUNITY SERVICE - Melyana R Pugu; Loso Judijanto; Romadhon (JOURNAL OF COMMUNITY DEDICATION, 2023)
This study aimed to assess the effect of an evidence-based character education intervention on students' positive behaviour. The research method used was a literature review. The results showed that the character education intervention designed and implemented based on empirical evidence had a significant and positive impact on students' behaviour. Specifically, findings indicated improvements in empathy, co-operation, social awareness and emotion management skills. Students who experienced evidence-based character education tended to show a decrease in negative behaviours such as aggression, bullying, and discipline infractions. Determinants of the effectiveness of such interventions include the quality and adherence of implementation, adaptation of content to the local context, and active involvement of teachers and teaching staff. The findings confirm the importance of adopting and implementing evidence-based character education programmes in school settings to promote the development of positive behaviours among students.